Transition metal oxide doped polyimide composite material and preparation method thereof
By introducing transition metal oxides and nano-scale reinforcers into polyimide composites, the performance degradation caused by the thermally conductive material's water absorption in humid environments is solved, and mechanical and thermal conductivity improvement and stability under high humidity conditions are achieved Improvement of sexuality.
Patent Information
- Application Number
- CN202411631848.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing thermally conductive materials absorb water in humid environments lead to dimensional changes and electrical properties, especially in high humidity conditions that affect their performance as insulating materials.
Using transition metal oxide doped polyimide composite materials, through the use of hydrophobic dianhydride monomers and diamine monomers, transition metal oxides, nano-scale reinforcement and other raw materials, through etherification modification and thermoforming technology, Composite materials with defects in improving hygroscopicity were prepared.
It significantly improves the mechanical properties, thermal conductivity and expansion resistance of the material, ensures stable performance in humid environments, and has versatility and is better than traditional polyimide composite materials.
Smart Images

Figure CN119192572A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyimide composite materials, in particular to a transition metal oxide-doped polyimide composite material and a preparation method thereof. Background Art
[0002] With the advancement of technology, thermal conductive materials are also developing. Current research hotspots include developing materials with higher thermal conductivity, reducing thermal resistance, improving the durability and stability of materials, and developing new thermal conductive materials with intelligent response characteristics. In addition, with the application of nanotechnology, nanoscale fillers are used to enhance the thermal conductivity of materials, which has also become an important development direction.
[0003] At present, the preparation of large-sized thermally conductive microsheets is conducive to reducing high interfacial thermal resistance and can fundamentally improve in-plane heat conduction. Among them, polyimide is a type of three-dimensional material. This is because polyimide is composed of linear or branched polymer chains, which are interconnected by chemical bonds to form a continuous three-dimensional network structure, which can provide a large-sized interface for thermal conductive materials and thus reduce thermal resistance. However, it will absorb moisture in a humid environment, resulting in dimensional changes and a decrease in electrical properties. Especially under high humidity conditions, the dielectric constant and loss tangent of polyimide will increase, affecting its performance as an insulating material. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a transition metal oxide doped polyimide composite material and a preparation method thereof, which utilizes etherification modification doping technology to impart new functional groups to effectively improve the thermal resistance change caused by hygroscopicity of existing thermal conductive materials, so as to solve the above-mentioned technical problems.
[0005] A transition metal oxide doped polyimide composite material, wherein the raw materials for preparation include, by weight: 4-6 parts of dianhydride monomer, 5-7 parts of diamine monomer, 0.1-0.3 parts of modifier, 0.2-0.6 parts of transition metal oxide, 2-4 parts of reinforcing agent, 0.08-0.1 parts of catalyst and / or dehydrating agent;
[0006] Wherein, the dianhydride monomer is a hydrophobic monomer.
[0007] Optionally, the dianhydride monomer is one or more of perfluorohexyl dianhydride (PFDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropanol) diphthalic anhydride (6FDA), pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-(hexafluoroisopropanol) benzophenonetetracarboxylic dianhydride (6FBA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (BPADA), and 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (BTDA).
[0008] Optionally, the diamine monomer is one or more of 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminodiphenyl ether (OMDA), 4,4'-diaminodiphenyl sulfone (DDS), p-phenylenediamine (PDA), 4,4'-diaminodiphenyl dimethyl biphenyl (BPDA), 3,3'-dimethyl-4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfone (DDS), and 2,2-bis(4-aminophenoxy)hexafluoropropane (6FDA-DAM).
[0009] Optionally, the modifier is one of 2-pyridylethylamine hydrochloride, cyclopentaneethylamine hydrochloride, 1-(4-iodophenyl)ethylamine hydrochloride, 2-fluoroethylamine hydrochloride, 2-(2-naphthyl)ethylamine hydrochloride, and hydroxyethylamine hydrochloride.
[0010] Optionally, the transition metal oxide is one or more of cobalt oxide, nickel oxide, molybdenum oxide, iron oxide, and copper oxide.
[0011] Optionally, the reinforcing agent is one or more of nano-ZnO, nano-SiO2, nano-BN sheets, and MXene nano-sheets.
[0012] Optionally, the catalyst is one or more of hexafluoroisopropanol, trimethylsilyl chloride, toluenesulfonic acid, pyridine, triethylamine, and acetic anhydride.
[0013] Optionally, the dehydrating agent is one or more of hexafluoroisopropanol, trimethylsilyl chloride, toluenesulfonic acid, pyridine, triethylamine, and acetic anhydride.
[0014] A method for preparing a transition metal oxide-doped polyimide composite material is used to prepare the above-mentioned transition metal oxide-doped polyimide composite material, and the preparation method comprises the following steps:
[0015] S1, select 4-6 parts of dianhydride monomer and 5-7 parts of diamine monomer, ultrasonically disperse them in 20mL N, N-dimethylacetamide, react at 35-50°C for 0.5-1h under an inert gas atmosphere, then react at 0°C for 3-5h, and then stand at room temperature for 24h to obtain a precursor solution;
[0016] Wherein, the dianhydride monomer is a hydrophobic monomer;
[0017] S2, selecting 0.1-0.3 parts of a modifier and dissolving it in 10 mL of N,N-dimethylformamide, and adding it to the precursor solution and reacting it at 50-80° C. for 3-5 hours to obtain a polyimide composite material network structure matrix;
[0018] S3, adding 0.2-0.6 parts of transition metal oxide, 2-4 parts of reinforcing agent and 0.08-0.1 parts of catalyst and / or dehydrating agent to the polyimide composite material network structure matrix, reacting at 80° C. for 24 hours to obtain a preform;
[0019] S4, pouring the preform into a mold, and obtaining a transition metal oxide-doped polyimide composite material through thermal forming.
[0020] Optionally, in S4, the thermal forming reaction conditions of the transition metal oxide-doped polyimide composite material are:
[0021] Placed in a flat vulcanizing press, at 20-70MPa / cm 2 Under pressure, react at 300°C for 2h.
[0022] The beneficial effects that the present invention can produce include:
[0023] The present invention provides a transition metal oxide doped polyimide composite material and a preparation method thereof. When preparing the transition metal oxide doped polyimide composite material, the selected monomer is a hydrophobic monomer, a hydrophobic functional group is introduced from the structure, a polyimide precursor solution with hydrophobic properties is obtained through reaction, and the carboxyl groups on the structure are further etherified to further enhance its hydrophobic properties and inhibit the change of thermal resistance due to moisture absorption; at the same time, by doping with transition metal oxides, the transition metal oxide doped polyimide composite material is superior to traditional polyimide composite materials in terms of mechanical properties, thermal conductivity, expansion coefficient and multifunctionality; and a nano-scale reinforcing agent can significantly improve the mechanical properties of the composite material. Due to the high specific surface area and strong interface interaction of the nanoparticles, they can effectively transmit stress, thereby improving the overall mechanical properties of the transition metal oxide doped polyimide composite material, and synergistically improving the thermal conductivity and reducing the expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the chemical reaction equation of the transition metal oxide-doped polyimide composite material of Example 1 of the present invention;
[0025] Figure 2 This is a schematic diagram of the surface water contact angle test of the transition metal oxide-doped polyimide composite material of Example 1 of the present invention;
[0026] Figure 3 It is a schematic diagram of the tensile strength test results of the transition metal oxide-doped polyimide composite material, preform and commercially available product of the present invention;
[0027] Figure 4 It is a schematic diagram of the thermal conductivity test results of the transition metal oxide-doped polyimide composite material, the preform and the commercially available product of the present invention;
[0028] Figure 5 It is a schematic diagram of expansion rate test results of the transition metal oxide doped polyimide composite material, preform and commercial product in the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Existing thermal conductive materials absorb moisture in a humid environment, resulting in dimensional changes and decreased electrical properties. In particular, under high humidity conditions, the dielectric constant and loss tangent of polyimide will increase, affecting its performance as an insulating material. To this end, the present invention provides a transition metal oxide-doped polyimide composite material to improve the hygroscopic defects of existing thermal conductive materials. Among them, the preparation raw materials include, by mass, 4-6 parts of dianhydride monomers, 5-7 parts of diamine monomers, 0.1-0.3 parts of modifiers, 0.2-0.6 parts of transition metal oxides, 2-4 parts of reinforcing agents, 0.08-0.1 parts of catalysts and / or dehydrating agents; wherein the dianhydride monomer is a hydrophobic monomer.
[0031] Furthermore, the dianhydride monomer is one or more of perfluorohexyl dianhydride (PFDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-hexafluoroisopropanol diphthalic anhydride (6FDA), pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-(hexafluoroisopropanol)benzophenonetetracarboxylic dianhydride (6FBA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (BPADA), and 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (BTDA).
[0032] Furthermore, the diamine monomer is one or more of 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminodiphenyl ether (OMDA), 4,4'-diaminodiphenyl sulfone (DDS), p-phenylenediamine (PDA), 4,4'-diaminodiphenyl dimethyl biphenyl (BPDA), 3,3'-dimethyl-4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfone (DDS), and 2,2-bis(4-aminophenoxy)hexafluoropropane (6FDA-DAM).
[0033] Furthermore, the modifier is one of 2-pyridylethylamine hydrochloride, cyclopentaneethylamine hydrochloride, 1-(4-iodophenyl)ethylamine hydrochloride, 2-fluoroethylamine hydrochloride, 2-(2-naphthyl)ethylamine hydrochloride, and hydroxyethylamine hydrochloride.
[0034] Furthermore, the transition metal oxide is one or more of cobalt oxide (Co2O3), nickel oxide (NiO), molybdenum oxide (MoO3), iron oxide (Fe2O3), and copper oxide (CuO).
[0035] Furthermore, the reinforcing agent is one or more of nano-ZnO, nano-SiO2, nano-BN sheets, and MXene nano-sheets.
[0036] Furthermore, the catalyst is one or more of hexafluoroisopropanol, trimethylsilyl chloride, toluenesulfonic acid, pyridine, triethylamine, and acetic anhydride.
[0037] Furthermore, the dehydrating agent is one or more of hexafluoroisopropanol, trimethylsilyl chloride, toluenesulfonic acid, pyridine, triethylamine, and acetic anhydride.
[0038] See also Figure 1-Figure 5 As shown, the present invention provides a method for preparing a transition metal oxide doped polyimide composite material, which is applied to prepare the above transition metal oxide doped polyimide composite material, and the preparation method comprises the following steps:
[0039] Step 1, select 4-6 parts of dianhydride monomer and 5-7 parts of diamine monomer and ultrasonically disperse them in 20mL N, N-dimethylacetamide, react for 0.5-1h under an inert gas protective atmosphere, then react for 3-5h at 0°C, and then stand at room temperature for 24h to obtain a precursor solution; wherein the dianhydride monomer is a hydrophobic monomer;
[0040] Step 2: 0.1-0.3 parts of a modifier is selected and dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution to react at 50-80° C. for 3-5 hours to obtain a network structure matrix of a polyimide composite material;
[0041] Step 3: Add 0.2-0.6 parts of transition metal oxide, 2-4 parts of reinforcing agent and 0.08-0.1 parts of catalyst and / or dehydrating agent to the network structure matrix of the polyimide composite material, and react at 80° C. for 24 hours to obtain a preform;
[0042] Step 4: pour the preform into a mold and obtain a transition metal oxide doped polyimide composite material by thermal forming. The thermal forming reaction conditions of the transition metal oxide doped polyimide composite material are:
[0043] Placed in a flat vulcanizing press, at 20-70MPa / cm 2 Under pressure, react at 300°C for 2h.
[0044] Example 1: Select 5 parts of 3,3'-dimethyl-4,4'-diaminodiphenylmethane (MDA) and 4 parts of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), ultrasonically disperse them in 20 mL of N,N-dimethylacetamide, and react at 35°C for 0.5 h under an inert gas protective atmosphere, then react at 0°C for 3 h, and then stand at room temperature for 24 h to obtain a precursor solution. Next, 0.1 parts of 2-(2-naphthyl)ethylamine hydrochloride was dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution to react at 70°C for 3 hours to obtain a network structure matrix of the polyimide composite material; then, 0.2 parts of cobalt oxide, 2 parts of nano-SiO2, and 0.08 parts of hexafluoroisopropanol and pyridine in a mass ratio of 1:1 were added to the network structure matrix of the polyimide composite material, and reacted at 80°C for 24 hours to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50 MPa / cm 2 The mixture was reacted at 300° C. under pressure for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the first product).
[0045] Example 2: 6 parts of 4,4'-diaminodiphenyl ether (ODA) and 6 parts of 4,4'-(hexafluoroisopropanol) benzophenone tetracarboxylic dianhydride (6FBA) were ultrasonically dispersed in 20 mL of N,N-dimethylacetamide, and reacted at 40°C for 1 h, then at 0°C for 4 h, and then allowed to stand at room temperature for 24 h to obtain a precursor solution; then, 0.2 parts of 2-pyridylethylamine hydrochloride were dissolved in 10 mL of N,N-dimethylacetamide. The preform was prepared by adding 0.2 parts of molybdenum oxide, 2 parts of nano-BN sheets and 0.1 parts of triethylamine and pyridine in a mass ratio of 2:1 to the network structure matrix of the polyimide composite material, and reacting at 80°C for 24 hours to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50MPa / cm 2 The mixture was reacted at 300° C. under pressure for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the second product).
[0046] Example 3: 6 parts of 3,3'-dimethyl-4,4'-diaminodiphenyl ether (OMDA) and 4,4'-diaminodiphenyl sulfone (DDS) in a mass ratio of 1:2 and 5 parts of pyromellitic dianhydride (PMDA) were ultrasonically dispersed in 20 mL of N,N-dimethylacetamide, and reacted at 45°C for 0.5 h, then at 0°C for 5 h, and then allowed to stand at room temperature for 24 h to obtain a precursor solution; then, 0.1 parts of hydroxyethylamine hydrochloride was dissolved in 10mL N,N-dimethylformamide was added to the precursor solution and reacted at 80°C for 4h to obtain a polyimide composite network structure matrix; then 0.4 parts of nickel oxide, 3 parts of MXene nanosheets and 0.1 parts of acetic anhydride and pyridine in a mass ratio of 1:1 were added to the polyimide composite network structure matrix, and reacted at 80°C for 24h to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the third product).
[0047] Example 4: Select 5 parts of 4,4'-diaminodiphenylmethane (MDA) and 4,4'-diaminodiphenyl sulfone (DDS) with a mass ratio of 2:3 and 6 parts of 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (BTDA) and ultrasonically disperse them in 20mL N,N-dimethylacetamide, and react at 50°C for 0.5h, then at 0°C for 4h, and then stand at room temperature for 24h to obtain a precursor solution; then, 0.1 parts of cyclopentaneethylamine hydrochloride are dissolved in 10mL N,N-dimethylformamide, and add it to the precursor solution and react at 50°C for 5 hours to obtain a polyimide composite network structure matrix; then add 0.4 parts of cobalt oxide and iron oxide in a mass ratio of 3:1, 3 parts of nano ZnO and 0.08 parts of trimethylchlorosilane and pyridine in a mass ratio of 5:3 to the polyimide composite network structure matrix, and react at 80°C for 24 hours to obtain a preform; pour the preform into a mold, and place the mold containing the preform in a flat vulcanizer at 50MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the fourth product).
[0048] Example 5: Select 5 parts of 4,4'-diaminodiphenyldimethylbiphenyl (BPDA) and 4,4'-diaminodiphenyl sulfone (DDS) in a mass ratio of 2:3 and 6 parts of perfluorohexyl dianhydride (PFDA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) in a mass ratio of 1:1, and ultrasonically disperse them in 20mL N,N-dimethylacetamide, and react at 40°C for 0.5h, then at 0°C for 5h, and then stand at room temperature for 24h to obtain a precursor solution; then, 0.2 parts of 1-(4-iodophenyl)ethylamine salt The salt was dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution to react at 70°C for 3 hours to obtain a polyimide composite network structure matrix; then, 0.3 parts of nickel oxide and copper oxide in a mass ratio of 2:1, 3 parts of nano ZnO and nano SiO2 in a mass ratio of 5:1, and 0.1 parts of triethylamine and acetic anhydride in a mass ratio of 1:2 were added to the polyimide composite network structure matrix, and reacted at 80°C for 24 hours to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50 MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the fifth product).
[0049] Example 6: Select 5 parts of 4,4'-diaminodiphenyl sulfone (DDS) and 2,2-bis(4-aminophenoxy)hexafluoropropane (6FDA-DAM) in a mass ratio of 1:3 and 6 parts of pyromellitic dianhydride (PMDA) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) in a mass ratio of 1:2, and ultrasonically disperse them in 20mL N,N-dimethylacetamide, and react at 40°C for 0.5h, then at 0°C for 5h, and then stand at room temperature for 24h under an inert gas protective atmosphere to obtain a precursor solution; then, 0.1 parts of 2-(2-naphthyl)ethylamine hydrochloride was dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution and reacted at 70° C. for 4 hours to obtain a polyimide composite network structure matrix; then 0.4 parts of molybdenum oxide and copper oxide in a mass ratio of 3:1, 2 parts of MXene nanosheets and 0.09 parts of toluenesulfonic acid were added to the polyimide composite network structure matrix, and reacted at 80° C. for 24 hours to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50 MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the sixth product).
[0050] Example 7: Select 5 parts of 3,3'-dimethyl-4,4'-diaminodiphenyl ether (OMDA) and 2,2-bis(4-aminophenoxy)hexafluoropropane (6FDA-DAM) in a mass ratio of 1:4 and 5 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (BTDA) in a mass ratio of 2:3, and ultrasonically disperse them in 20 mL of N,N-dimethylacetamide, and react at 45°C for 1 hour under an inert gas protective atmosphere, then react at 0°C for 4 hours, and then stand at room temperature for 24 hours to obtain a precursor solution ; Then, 0.2 parts of 1-(4-iodophenyl)ethylamine hydrochloride was dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution at 50° C. for reaction for 5 hours to obtain a polyimide composite network structure matrix; then, 0.6 parts of cobalt oxide and nickel oxide in a mass ratio of 1:5, 2 parts of ZnO and nano BN sheets in a mass ratio of 3:1, and 0.1 parts of pyridine were added to the polyimide composite network structure matrix, and the temperature was raised to 80° C. for reaction for 24 hours to obtain a preform; the preform was poured into a mold, and the mold containing the preform was placed in a flat vulcanizer at 50 MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the seventh product).
[0051] Example 8: 7 parts of p-phenylenediamine and 4,4'-diaminodiphenyl sulfone (DDS) in a mass ratio of 5:1 and 6 parts of 4,4'-(hexafluoroisopropanol) diphthalic anhydride (6FDA) and 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA) and 4,4'-(hexafluoroisopropanol) benzophenone tetracarboxylic dianhydride (6FBA) in a mass ratio of 2:2:3 were ultrasonically dispersed in 20 mL of N,N-dimethylacetamide, and reacted at 50°C for 0.5h, then at 0°C for 5h, and then allowed to stand at room temperature for 24h to obtain a precursor solution; then, 0.3 parts of 1-(4-iodophenyl) ethyl Amine hydrochloride is dissolved in 10 mL of N,N-dimethylformamide, and added to the precursor solution to react at 70°C for 3 hours to obtain a network structure matrix of a polyimide composite material; then, 0.5 parts of cobalt oxide, iron oxide and copper oxide in a mass ratio of 1:1:3, 3 parts of ZnO, nano-SiO2 and nano-BN sheets in a mass ratio of 1:1:1 and 0.08 parts of hexafluoroisopropanol, toluenesulfonic acid and triethylamine in a mass ratio of 4:2:3 are added to the network structure matrix of the polyimide composite material, and reacted at 80°C for 24 hours to obtain a preform; the preform is poured into a mold, and the mold containing the preform is placed in a flat vulcanizer at 50 MPa / cm 2 Under pressure, the reaction was carried out at 300° C. for 2 hours to obtain a transition metal oxide-doped polyimide composite material (the eighth product).
[0052] In the present invention, the transition metal oxide doped polyimide composite material prepared above can be used to make a thermal conductive layer. When preparing the transition metal oxide doped polyimide composite material, the selected monomer is a hydrophobic monomer, a hydrophobic functional group is introduced from the structure, a polyimide precursor solution with hydrophobic properties is obtained by reaction, and the carboxyl groups on the structure are further etherified to further enhance its hydrophobic properties and inhibit the change of thermal resistance due to moisture absorption; at the same time, by doping with transition metal oxides, the transition metal oxide doped polyimide composite material is superior to traditional polyimide composite materials in mechanical properties, thermal conductivity, expansion coefficient and multifunctionality; and the nano-scale reinforcing agent can significantly improve the mechanical properties of the composite material. Due to the high specific surface area and strong interface interaction of the nanoparticles, they can effectively transmit stress, thereby improving the overall mechanical properties of the transition metal oxide doped polyimide composite material, and synergistically improving the thermal conductivity and reducing the expansion coefficient.
[0053] In the above, refer to Figure 2-Figure 5 As shown, the present invention conducts water contact angle test, mechanical property test and thermal property test on the transition metal oxide doped polyimide composite materials prepared in Examples 1-8. Specifically, Figure 2The schematic diagram of the surface water contact angle test of the transition metal oxide doped polyimide composite material of Example 1, wherein Figure a, Figure b, Figure c and Figure d are schematic diagrams of the process of dripping the liquid to be tested onto the surface of the transition metal oxide doped polyimide composite material. It can be seen from Figure d that the water contact angle of the transition metal oxide doped polyimide composite material can reach 159.8°, which is much larger than 90°. It can be explained that by doping with transition metal oxides, the polyimide composite material belongs to the hydrophobic category. It is worth noting that generally the water contact angle is within 90°, indicating that the liquid tends to spread on the surface of the material, and this surface is called a hydrophilic surface; when the water contact angle is 90-150°, it indicates that the liquid tends to form beads and roll on the surface of the material and is not easy to spread, and this surface is called a hydrophobic surface; and when the water contact angle is greater than 150°, the surface of the material is considered to be super hydrophobic. Among them, Figure 3 , Figure 4 and Figure 5 Schematic diagrams of the test results of tensile strength, thermal conductivity and expansion rate of the transition metal oxide-doped polyimide composite materials prepared in Examples 1-8, and the preforms and commercial products prepared from the network structure matrix of the polyimide composite material not doped with transition metal oxides; Figure 3 It can be seen that the first to eighth products adopt chemical modification to prepare cross-linked network structure polyimide composite materials, and use transition metal doping to further improve their tensile strength (compared with commercially available products). The tensile strength of the transition metal oxide doped polyimide composite materials can reach 2000MPa, and they have strong mechanical properties. Figure 4 It can be seen that compared with the commercially available products, the first to eighth products are cross-linked network structures prepared by the present invention, and the heat conduction can reach 2W·m -1 ·K -1 , effectively improving its thermal conductivity. Among them, the third and fourth products use a higher content of transition metal oxides, and their thermal conductivity is higher than that of other products. It can be concluded that the cross-linked network structure and the doping of transition metal oxides synergistically improve its thermal conductivity. Figure 5 It can be seen that by conducting water absorption and expansion tests on the first to eighth products, the anti-expansion effect can be achieved.
[0054] In the above, the test methods for water contact angle test, mechanical property test and thermal property test of transition metal oxide doped polyimide composite material are as follows:
[0055] 1) Water contact angle test: The transition metal oxide-doped polyimide composite material of Example 1 was cut into samples of 10×30 mm, pasted on a glass plate, and a drop of deionized water was added to the surface of the sample and the reading was taken. Three points were tested for each sample and the results were averaged.
[0056] 2) Tensile performance test: According to GB / T1040.3-2006, the transition metal oxide-doped polyimide composite materials prepared in Examples 1-8, the preforms described above, and the commercially available products were made into dumbbells with a length of 110 mm, and were clamped on fixtures for tensile testing; wherein the fixture spacing was 80 mm, the sensor test pressure was 500 N, and the tensile rate was 10 mm / min; for each group of experiments, 3 groups of samples with the same performance were selected for parallel testing, and the test results were averaged to obtain the test results.
[0057] 3) Thermal conductivity test: The thermal diffusion coefficients of the transition metal oxide-doped polyimide composite materials prepared in Examples 1-8, the preforms described above, and the commercially available products were measured using a German NETZSCH LFA467 laser thermal conductivity meter, and the thermal conductivity was calculated using the following formula: thermal conductivity = density × specific heat capacity × thermal diffusion coefficient.
[0058] 4) Expansion rate test: 0.5 g of the transition metal oxide-doped polyimide composite material prepared in Examples 1-8, the preforms mentioned above, and commercially available products were respectively selected and immersed in 30,000 mL of water for 24 h. The surface moisture was wiped off and weighed. The expansion rate was: (water absorption mass - mass before water absorption) / mass before water absorption × 100%.
Claims
1. A transition metal oxide doped polyimide composite material, characterized in that: The raw materials for preparation include, by weight: 4-6 parts of dianhydride monomer, 5-7 parts of diamine monomer, 0.1-0.3 parts of modifier, 0.2-0.6 parts of transition metal oxide, 2-4 parts of reinforcing agent, 0.08-0.1 parts of catalyst and / or dehydrating agent; Wherein, the dianhydride monomer is a hydrophobic monomer.
2. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The dianhydride monomer is one or more of perfluorohexyl dianhydride (PFDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropanol) diphthalic anhydride (6FDA), pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-(hexafluoroisopropanol) benzophenonetetracarboxylic dianhydride (6FBA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (BPADA), and 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (BTDA).
3. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The diamine monomer is one or more of 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminodiphenyl ether (OMDA), 4,4'-diaminodiphenyl sulfone (DDS), p-phenylenediamine (PDA), 4,4'-diaminodiphenyl dimethyl biphenyl (BPDA), 3,3'-dimethyl-4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfone (DDS), and 2,2-bis(4-aminophenoxy)hexafluoropropane (6FDA-DAM).
4. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The modifier is one of 2-pyridylethylamine hydrochloride, cyclopentaneethylamine hydrochloride, 1-(4-iodophenyl)ethylamine hydrochloride, 2-fluoroethylamine hydrochloride, 2-(2-naphthyl)ethylamine hydrochloride and hydroxyethylamine hydrochloride.
5. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The transition metal oxide is one or more of cobalt oxide, nickel oxide, molybdenum oxide, iron oxide and copper oxide.
6. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The reinforcing agent is one or more of nano ZnO, nano SiO2, nano BN sheet, and MXene nano sheet.
7. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The catalyst is one or more of hexafluoroisopropanol, trimethylchlorosilane, toluenesulfonic acid, pyridine, triethylamine and acetic anhydride.
8. The transition metal oxide-doped polyimide composite material according to claim 1, characterized in that: The dehydrating agent is one or more of hexafluoroisopropanol, trimethylsilyl chloride, toluenesulfonic acid, pyridine, triethylamine, and acetic anhydride.
9. A method for preparing a transition metal oxide-doped polyimide composite material, characterized in that: The method is applied to prepare the transition metal oxide-doped polyimide composite material according to any one of claims 1 to 8, and the preparation method comprises the following steps: S1, select 4-6 parts of dianhydride monomer and 5-7 parts of diamine monomer, ultrasonically disperse them in 20mL N, N-dimethylacetamide, react at 35-50°C for 0.5-1h under an inert gas atmosphere, then react at 0°C for 3-5h, and then stand at room temperature for 24h to obtain a precursor solution; Wherein, the dianhydride monomer is a hydrophobic monomer; S2, selecting 0.1-0.3 parts of a modifier and dissolving it in 10 mL of N,N-dimethylformamide, and adding it to the precursor solution and reacting it at 50-80° C. for 3-5 hours to obtain a polyimide composite material network structure matrix; S3, adding 0.2-0.6 parts of transition metal oxide, 2-4 parts of reinforcing agent and 0.08-0.1 parts of catalyst and / or dehydrating agent to the polyimide composite material network structure matrix, reacting at 80° C. for 24 hours to obtain a preform; S4, pouring the preform into a mold, and obtaining a transition metal oxide-doped polyimide composite material through thermal forming.
10. The method for preparing a transition metal oxide-doped polyimide composite material according to claim 9, characterized in that: In S4, the thermal forming reaction conditions of the transition metal oxide-doped polyimide composite material are: Placed in a flat vulcanizing press, at 20-70MPa / cm 2 Under pressure, react at 300°C for 2h.
Citation Information
Patent Citations
Aromatic diamine, preparation method thereof, method for preparing polyimide from aromatic diamine and prepared polyimide
CN110156661A
Flexible polyimide composite material with low dielectric constant and preparation method thereof
CN118684887A
Interpenetrating network type polyimide molding powder, preparation method and product
CN118812881A
Polyasparagine derivative and method for producing the same
JP2002293929A
Polyimides as dielectrics
US20150029638A1
